Pertanggungjawaban pidana korporasi dalam cyber pornografi - Hatarto Pakpahan; Crisjiatmoko Mindika Dwimaylando (Jurnal Cakrawala Hukum, 2021)
Writing this article aims to identify and analyze the position of corporations as legal subjects in cyber pornography and forms of corporate criminal liability as active actors and corporations as passive actors in their position as online communication intermediaries as platform providers that can be accessed by the public. In this journal article, normative legal research is used. Corporations as legal subjects are recognized in the ITE Law Article 27 (1) in conjunction with article 52 paragraph 4, but the definition of the corporation itself is vague considering that the ITE Law is not explained especially in general criminal law (KUHP) which does not recognize corporations as legal subjects who can be held criminally responsible. In cyber pornography, corporate criminal liability in terms of corporations acting as active actors can be charged with Article 45 paragraph (1) in conjunction with Article 52 paragraph 4 of the ITE Law and also Article 40 paragraph (7) of Law 44. of 2008 concerning Pornography, but in the case of corporations act as passive actors, namely as intermediaries for online communication or as platform providers, cannot be held criminally responsible because there are no regulations that regulate it.How to cite item: Pakpahan, H., Dwimaylando, C., (2021). Pertanggungjawaban pidana korporasi dalam cyber pornografi. Jurnal Cakrawala Hukum, 12(3), 274-283. doi:https://doi.org/10.26905/idjch.v12i3.7092.